Anti-Corruption Policy in the Field of Public Management of the Social Sector in the Context of Decentralization - I. Ryzhuk; О. Bryhinets; О. Halus (Юридичний часопис Національної академії внутрішніх справ, 2021)
The purpose of the study is to analyze the relationship between the reform of public decentralization in Ukraine in the field of social governance and anti-corruption policy, as well as to develop scientifically sound recommendations for improving legislation to prevent corruption in local government. Methodology. In the process of scientific research a set of philosophical and worldview, general scientific and special scientific methods was used. The axiological approach was used to clarify the role and importance of proper legislative regulation of the outlined social relations that arise in decision-making at the municipal level. The method of analysis and synthesis facilitated the analysis of the concept, features, object, parties and conditions of decentralization. Of the special scientific research methods used in the article, systemic and structural-functional, comparative-legal. Scientific novelty. It was emphasized that with the beginning of the reform of decentralization of public power, capable united territorial communities began to be created, capable of independently providing quality public services to the population, providing organizational and legal guarantees for their residents to exercise their constitutional right to social protection. It is stated that many positive transformations that are carried out in our state are leveled, first of all, at the local level due to the large-scale spread of corruption. Given the lack of a special strategic document on anti-corruption, the draft law analyzed the work of parliament on resolving the issue of anti-corruption strategy, in particular, attention was paid to the draft Law "On Principles of State Anti-Corruption Policy for 2020–2024". It has been proven that corruption negatively affects the state’s reputation in the international community, which hinders the attraction of foreign investment and poses a threat to domestic social and economic security. Due to the fact that fraud with budget funds causes obvious damage to the social functions of the state, corruption at the municipal level is often the most harmful, because it makes the most vulnerable segments of the population more vulnerable. It is determined that at the state level the legislative base is updated, concepts and programs of corruption prevention are adopted, own anti-corruption institutional model of organization of public administration is formed. It was stated that corruption continues to play a negative role in public administration, and the means and methods aimed at its prevention remain ineffective. Conclusions. Ways to increase the level of anti-corruption policy in the field of public management of the social sector in the context of decentralization are proposed. It was concluded that local self-government bodies should improve the current anti-corruption legislation by supplementing the list of entities that approve anti-corruption programs